2015
DOI: 10.1111/inm.12143
|View full text |Cite
|
Sign up to set email alerts
|

Maturing out, natural recovery, and dual diagnosis: What are the implications for older adult mental health services?

Abstract: In 1962, Charles Winick proposed that addiction was a self-limiting process, whereby individuals stopped using substances once the stresses of life transitions ceased. The notion of maturing out, as labelled by Winick, often forms the basis of the natural recovery movement in alcohol and other drug (AOD) research, aiding the notion that older individuals either cease their substance use or fall victim to the higher mortality rates prevalent in substance-using populations. As more consumers present to adult men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The mean drinking per day reported was 8.5 drinks, so many people may quit by switching to alcohol, even though 35% reported that alcohol was a trigger (Toneatto et al, 1999). One study suggests that many older, dually diagnosed adults do not recover without treatment (Searby et al, 2015).…”
Section: Cocainementioning
confidence: 99%
“…The mean drinking per day reported was 8.5 drinks, so many people may quit by switching to alcohol, even though 35% reported that alcohol was a trigger (Toneatto et al, 1999). One study suggests that many older, dually diagnosed adults do not recover without treatment (Searby et al, 2015).…”
Section: Cocainementioning
confidence: 99%
“…Despite these findings, little research explores dual diagnosis in the older adult (65 years and over) population. Older adults pose substantial challenges in respect of screening and assessment of alcohol and other drug (AOD) use, and have been labelled the “invisible addicts” as their presentations may differ markedly from their younger counterparts (Crome et al ; Searby et al ).…”
Section: Introductionmentioning
confidence: 99%